Baseline design of a subsea shuttle tanker system for liquid carbon dioxide transportation. (15th November 2021) - Ma, Yucong; Xing, Yihan; Ong, Muk Chen; Hemmingsen, Tor Henning
Abstract: This paper presents the baseline design of a 34, 000-tonne subsea shuttle tanker (SST). The SST is proposed as an alternative to subsea pipelines and surface tankers for the transportation of liquid carbon dioxide (CO2 ) from existing offshore/land facilities to marginal subsea fields. In contrast to highly weather-dependent surface tanker operations, the SST can operate in any condition underwater. The SST is an electric-powered autonomous underwater vehicle with a length and beam of 164 m and 17 m, respectively. It has a cargo carrying capacity of 16, 362 m 3 . This capacity is sufficient to allow the SST to fulfil the annual storage demands of ongoing carbon capture and storage (CCS) projects in Norway. It travels with a slow speed of 6 knots at 70 m constant water depth for maximum energy efficiency and offloads CO2 via a connected coupling to the subsea well where CO2 is directly injected. To be economically attractive, the SST has a high payload of 50% displacement which makes a low structural weight design extremely crucial. This is achieved by employing a double hull design for the SST with active pressure compensating systems to cope with the large collapse pressure loads underwater. Highlights: A baseline design of the large electric-powered autonomous subsea shuttle tanker is presented. A double hull design is utilised to mitigate the collapse pressure in the mid-body external hull. Major specifications and features such as CO2 properties, structural properties, and hydrodynamic properties are discussed. The vessel has high payload capacity and slow service speed to maximise transportation capacity with minimum energy cost.